BENTUK, FUNGSI, DAN MAKNA LELAKAQ SASAK SEBAGAI MEDIA KAMPANYE CALON WALIKOTA MATARAM - Usman Jayadi (Center of Language and Cultural Studies, 2017)
In Lombok Island, Lelakaq Sasak is one of the important cultures used to give suggestion to people. Nowdays Lelakaq Sasak are used as campaign media e.g. elections for head village, legislative, regency and governor to attract constituent. The goal of this research is to know how Lelakaq types and function used in Mataram regency campaign. Data were collected using observation, quotation, document, and were analyzed using structural analysis, semiotic and hermeneutic. The results showed some types of Lelakaq used for campaing in Mataram regency election existed. Structural analysis found Lelakaq was used in terms of theme and advice. In semiotic, Lelakaq was presented in terms of metaphor, hyperbola. In hermeneutic Lelakaq apperead in terms of sounds, aliteration, association, diction. Lelakaq functioned as entertaint, stimulus and advice. The purpose of Lelakaq is about to describe event and feeling and in the campaign lelakaq was represented to give moral value, material, spiritual and people’s visualisation.